Pelatihan Penulisan Karya Ilmiah bagi Guru SMK Negeri 3 Jeneponto - Fajriani Azis; Asmar Asmar; Magfirah Wahyu Ramadhani; Ambarwati Akib; M. Ridwan Tikollah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This study is designed to improve the writing skills of teachers at SMK Negeri 3 Jeneponto by offering training on how to write scientific articles that conform to journal requirements. The research uses interactive lectures and group discussions, allowing teachers to actively participate in conversations to deal with difficulties and come up with solutions in scientific writing. The findings indicate that the training effectively enhanced teachers' ability to find scientific sources, write articles that meet academic standards, and choose suitable journals for publication. Furthermore, the teachers showed strong enthusiasm for conducting Classroom Action Research (CAR) and expressing their ideas through scientific writing. As a result, this training helps to boost teacher professionalism and the overall quality of education at SMK Negeri 3 Jeneponto.